182k views
4 votes
Determine k so that, when x^3 + kx^2 - kx + 1 is divided by (x-2) the remainder is 3.

1 Answer

4 votes

Given that:

x³ + kx² - kx + 1 divide by (x - 2), has a remainder of 3

Let f(x) = x³ + kx² - kx + 1

When f(x) is divided by (x 2), the remainder is =3

This is the remainder theorem:

So,

f(2) = 2³ + k(2)² - 2k + 1 = 3

8 + 4k - 2k + 1 = 3

let's collect like terms

4k - 2k + 8 + 1 = 3

2k + 9 = 3

lets subtract 9 from both sides

2k = 3 - 9

2k = -6

divide both sides by 2

k = -6/2

k = -3

User Shaun Jackman
by
5.5k points